THU0169 Persistence of Tofacitinib in The Treatment of Rheumatoid Arthritis in Open-Label, Long-Term Extension Studies up To 7 Years. (15th July 2016) - Pope, J.; Keystone, E.; Jamal, S.; Wang, L.; Fallon, L.; Woolcott, J.; Lazariciu, I.; Haraoui, B.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for treatment of rheumatoid arthritis (RA). Open-label, long-term extension (LTE) studies have enrolled tofacitinib-treated patients (pts) to evaluate safety and efficacy over time. Time on treatment is considered a composite measure of efficacy and safety; discontinuation (D/C) is often due to lack of efficacy (LOE) and/or adverse events (AEs) for disease-modifying antirheumatic drugs (DMARDs). 1 Objectives: To estimate drug survival of tofacitinib up to 84 months (mo) in LTE studies and describe reasons for D/C. Methods: Data were pooled from two LTE studies (NCT00413699 [up to April 2014; study ongoing, database unlocked] and NCT00661661 [completed]). Of 6553 pts from Phase (P) 1, 2 and 3 studies, 4858 pts (74.1%) received treatment in LTE studies. Tofacitinib 5 or 10 mg BID were initiated as monotherapy or with background DMARDs; pooled data and data for each dose ± background DMARDs were analysed. Pts were assigned tofacitinib 5 or 10 mg BID based on average daily dose in LTE. Kaplan-Meier (K-M) analyses estimated drug survival in tofacitinib-treated pts who withdrew for any reason, due to LOE or due to AE in the LTE, including pts who had previously responded to and tolerated treatment in P1P2P3 studies. Ongoing pts were censored as of April 2014, while pts completing the trial(s) were censored at their completion date. Safety data were included over 84 mo and efficacy data up to 72 mo due to limited pt numbers after 72 mo for efficacy. Retention data were divided into dose and mono vs combination therapy. Results: 4858 pts were treated for a mean (maximum) duration of 2.5 (6.9) years (yrs) (results previously reported). 2 Overall, median survival for all tofacitinib treated pts was 5.2 yrs [95% CI 5.0, 5.6] (Figure 1 ). Median survival for pts receiving tofacitinib with background DMARDs or as monotherapy was 5.3 [4.9, 5.7] and 5.4 [4.8, not evaluable] yrs, respectively. K-M estimates appear similar between 5 and 10 mg BID, median survival was 5.4 [4.9, 5.9] and 5.0 [4.7, 5.5] yrs, respectively (Figure 1 ). The D/C rate due to LOE was considerably lower than due to AEs (AEs: 17.8%, 22.9%, 15.6%; LOE: 2.7%, 3.3%, 2.5% for all tofacitinib, 5 or 10 mg BID, respectively). The most commonly reported reasons for D/C due to AEs by class were infections/infestations (7.2%, 7.8%, 7.0%), investigations (3.1%, 4.6%, 2.5%) and neoplasms (benign, malignant, unspecified) (2.7%, 3.9%, 2.1%) for all tofacitinib, 5 or 10 mg BID, respectively. Conclusions: Drug survival in LTE studies provides early information on the long-term safety, efficacy and tolerability of a therapy. In this analysis, median survival of tofacitinib was approximately 5 yrs, with D/C more commonly associated with AEs than LOE. Similar survival medians were observed for the 5 and 10 mg BID dose groups and monotherapy vs background DMARD therapy. These data support the use of tofacitinib for long-term management of RA. References: Neovius M et al. Ann Rheum Dis 2015; 74: 354–360. Wollenhaupt J et al. Arthritis Rheumatol 2014; 66: S375. Acknowledgement: This study was sponsored by Pfizer Inc. Editorial support was provided by CMC (funded by Pfizer Inc). Disclosure of Interest: J. Pope Grant/research support from: Pfizer, Consultant for: Pfizer, E. Keystone Grant/research support from: Pfizer, Consultant for: Pfizer, Speakers bureau: Pfizer, S. Jamal Grant/research support from: Pfizer, Consultant for: Pfizer, L. Wang Shareholder of: Pfizer, Employee of: Pfizer, L. Fallon Shareholder of: Pfizer, Employee of: Pfizer, J. Woolcott Shareholder of: Pfizer, Employee of: Pfizer, I. Lazariciu Consultant for: Pfizer, Employee of: Quintiles Inc, B. Haraoui Grant/research support from: Pfizer, Consultant for: Pfizer